Immunogold-EM analysis reveal brefeldin a-sensitive clusters of auxin in Arabidopsis root apex cells - U. Mettbach (Communicative & Integrative Biology, 2017)
Immunogold electron microscopy (EM) study of Arabidopsis root apices analyzed using specific IAA antibody and high-pressure freeze fixation technique allowed, for the first time, vizualization of subcellular localization of IAA in cells assembled intactly within plant tissues. Our quantitative analysis reveals that there is considerable portion of IAA gold particles that clusters within vesicles and membraneous compartments in all root apex cells. There are clear tissue-specific and developmental differences of clustered IAA in root apices. These findings have significant consequences for our understanding of this small molecule which is controlling plant growth, development and behavior.